Simulation of reforms of direct and indirect taxation for France - François Laisney; Martin Mühleisen; Matthias Staat; Stefan Vögele (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1992)
We study the welfare effects of combining the European Commission's proposal for VAT harmonization with different degrees of weakening of the 'quotient familial' , a feature of the French system of direct taxation which can be interpreted as aiming at taxing 'equivalised' household income. We compare two approaches to the calibration of the baseline situation and to the simulation of reactions to changes in the tax system. One of these takes fixed costs of work into account. For both we find that a tentative implementation of the Commission's proposal, keeping the low rate unchanged, is favourable to a narrow majority (the status quo is preferred on a number of criteria), but that it results in a high VAT rate in excess of the proposal. While a weakening of the quotient familial brings this rate within the desired bracket, the combined reform appears much less desirable than the pure VAT reform. This goes some way against the notion that the quotient familial constitutes a tax relief which is only significant for richer households.
Keywords: 330; Familienbesteuerung; Umsatzsteuer; Steuerreform; Simulation; Frankreich